Attitudes to fluorosis and dental caries by a response latency method - Williams DM, Chestnutt IG, Bennett PD, Hood K, Lowe R, Heard P. (Blackwell Synergy, 2006)
Understanding socially relevant attitudes to fluorosis and dental caries is important